'Knowing me, knowing you': an exploration of the views and experiences of nursing home residents and staff on their nursing home as 'home'. Issue 4 (8th April 2023) - Ryan, Assumpta A.; Moore, Kevin
Abstract: The overall aim of this grounded theory study was to explore the context of a nursing home as 'home' from the perspective of residents and staff. Sixteen focus group interviews were used to collect qualitative data from nursing home residents (N = 48) and staff (N = 44). Five distinct categories captured the views and experiences of participating residents and staff. These were: (a) Starting off on the right foot, 'First impressions can be the lasting ones; (b) Making new and maintaining existing connections, 'There is great unity between staff and residents'; (c) The nursing home as home, 'It's a bit like home from home for me'; (d) Intuitive knowing, 'I don't even have to speak, she just knows'; and (e) Feeling at home in a regulated environment, 'It takes the home away from nursing home'. Together these five categories formed the basis of the core category 'Knowing me, knowing you', which captures the experiences of participants who repeatedly highlighted the importance of relationships and feelings of mutuality and respect between and among staff and residents as central to feeling at home in a nursing home. The reciprocity and mutuality associated with the core category, 'Knowing me, knowing you', was at times challenged by staff shortages, time constraints, and conflicting priorities associated with the co-existence of a regulated and homely environment.